Energy Conversions Associated With Magnetic Reconnection. Issue 1 (8th January 2021) - Fadanelli, S.; Lavraud, B.; Califano, F.; Cozzani, G.; Finelli, F.; Sisti, M.
Abstract: We present theoretical and computational analyses of energy conversions in a magnetized collisionless plasma. We first revisit the theoretical approach to energy conversion analysis and discuss the expected correlations between the different conversion terms. We then present results from a Hybrid‐Vlasov simulation of a turbulent plasma, focusing on the immediate vicinity of a reconnection site. Energy transfers are examined locally and correlations between them are discussed in detail. We show a good anticorrelation between pressure‐driven and electromagnetic acceleration terms. A similar but weaker anticorrelation is found between the heat flux and thermodynamic work acting on internal energies. It is the departure from these anticorrelations that drives the effective changes in the species' kinetic and internal energies. We also show that overall energy gain or loss is statistically related to the local scale of the system, with higher conversion rates occurring mostly at the smallest local plasma scales. To summarize, we can say that the energization and de‐energization of a plasma is the result of the complex interplay between multiple electromagnetic and thermodynamic effects, which are best taken into account via such a point‐by‐point analysis of the system. Key Points: We present a novel approach to investigate energy conversions point‐by‐point in a plasma, using a multifluid framework We test the method on a reconnection site generated during the development of plasma turbulence in a hybrid Eulerian simulation Energy conversions follow from approximate force balance and near‐polytropy, and depend on local characteristic length scales